Changes of zinc, copper, and iron levels in the lung of male rats after subacute (4-week) and subchronic (13-week) exposure to formaldehyde - Özen, OA; Songur, A; Sarsilmaz, M; Yaman, M; Kus, I (Wiley-Liss, 2003)
The medical use of formaldehyde has focused especially on laboratory use. Harmful effects of formaldehyde inhalation, such as nasal squamous cell carcinoma, are quite well documented. However, detailed studies of the mechanisms of the damaging effects of formaldehyde on lung tissue are quite limited. Amounts of such elements as zinc, copper, and iron within lung tissue indicate whether or not they function physiologically. In this study, 36 adult albino Wistar male rats (6 animals per group) were exposed to 0 (Control), 5, and 10 ppm (1 ppm (sic) 1.2 mg/m(3)) of formaldehyde gas for subacute (4-week) and subchronic (13-week) periods. Whole-body exposure was continuously carried out for 8 h/day, 5 days/week. Body weights were recorded weekly. Levels of metals mentioned above were measured in lung tissue by atomic absorption spectrometry using wet ashing and were then compared with levels in the control groups. At the end of the study, a gradual decrease in weight gain, a decrease in zinc levels, and an increase in iron levels were observed in both subacute and subchronic groups compared to control groups. Statistically significant increases in tissue Fe levels were seen in the 10 ppm subacute (P < 0.001), 5 ppm subchronic (P < 0.001). and 10 ppm subchronic (P < 0.001) groups. We conclude that subacute or subchronic exposure to cytotoxic concentrations of formaldehyde may cause growth retardation and alter the trace element levels of zinc and iron in the lung tissue.
Keywords: zinc; copper; iron; formaldehyde toxicity; lung